Early Postoperative Ondansetron Exposure is Associated with Reduced 90-Day Mortality in Patients Undergoing Cardiac Surgery - Xiong, Dexin; Xiong, Chao (Frontiers in Surgery, 2022)
Background: Ondansetron is a widely used anti-emetic for the prevention and treatment of nausea and vomiting for patients in critical care. Recent retrospective cohort studies suggest the potential beneficial effects of ondansetron in critically ill patients. In this study, we investigate the impact of ondansetron use on patient outcomes after cardiac surgery. Material and Methods: The MIMIC- III database was used to identify cardiac surgical patients who had and had not early ondansetron use in the first 48 h in the postoperative period. Multivariable logistic regression was used to investigate the effect of ondansetron exposure on 90-day mortality, acute kidney injury, and malignant ventricular arrhythmias. Sensitivity analyses utilizing inverse-probability of treatment weighting and covariate balancing propensity score models were conducted to test the robustness of our findings. Results: 12.4% of patients received ondansetron. Ondansetron use was associated with lower risk of 90-day mortality in the multivariable logistic regression model (OR: 0.31, 95% CI: 0.13 to 0.72; P = 0.006) and sensitivity analyses. Additionally, ondansetron exposure was associated with less postoperative acute kidney injury (OR: 0.82, 95%CI: 0.69 to 0.96; P = 0.017) but did not increase the risk of postoperative malignant ventricular arrhythmias (OR: 0.38, 95%CI: 0.09 to 1.16; P = 0.191). Conclusions: In a population of cardiac surgical patients, early postoperative use of ondansetron appears to be associated with decreased 90-day mortality and acute kidney injury.